THE IMPACT OF UNEMPLOYMENT AND POVERTY LEVELS ON THE ECONOMY OF SOUTH SUMATRA - Angelica, Anggun; Yahya, Bella Desvi; Putri, Helen Amelia; Fakhirah, Nailah; Rahmawati, Tri Putri; Apriani, Rizki; M. Imami Akbar; Gufito Ramadhan (CV. Era Digital Nusantara, 2023)
This research is to determine the effect of unemployment and poverty on economic growth in South Sumatra Province in 2020-2022. The purpose of this study was to determine the effect of unemployment and poverty on economic growth in South Sumatra Province. The results of the study show that unemployment and poverty affect economic growth in South Sumatra Province. The results of this analysis indicate that unemployment and poverty rates have a significant impact on the economy of the people of South Sumatra. High unemployment rates lead to low people's incomes, lack of purchasing power, and reduced consumption.